Peran PPKn Sebagai Sarana Pendidikan Hukum Dalam Meningkatkan Kesadaran Peserta Didik Mematuhi Tata Tertib Sekolah di SMA Negeri 8 Surakarta Tahun Pelajaran 2021/2022 - Dewi Gilang; Yusuf Yusuf; Sugiaryo Sugiaryo (Prodi PPkn Universitas Slamet Riyadi, 2022)
The purpose of this study is to determine the role of PPKn as a means of legal education in raising awareness of students complying with the school rules of SMA Negeri 8 Surakarta for the 2021/2022 academic year. This research is descriptive qualitative. The data source uses both primary and secondary. Data collection techniques through interviews, observation and documentation. In order for the data to be valid, a triangluation of sources and techniques is carried out. Analyzed using interactive qualitative techniques. Based on data analysis, it can be concluded: The role of PPKn as a means of legal education in increasing awareness of the rights and obligations of students is really like getting facilities. The role of PPKn as a means of legal education in increasing awareness of student attendance is really like being present on time. The role of PPKn as a means of legal education in increasing awareness of the neatness of students is true as in full uniform. The role of PPKn as a means of education hukum in increasing awareness of student hygiene is indeed true such as participating in community service work activities.